ANALISIS SISTEM PENGENDALIAN INTERNAL PADA PERUMDA PASAR KOTA BITUNG SEBELUM DAN SETELAH PENGGELEDAHAN OLEH KEJAKSAAN - Ngangi, Syalomita; William A. Luntungan; Feiby N. Wantah; Monika I. K. Sukatno (JAD : Jurnal Riset Akuntansi & Keuangan Dewantara, 2024)
This study aims to analyze the internal control system implemented by the Regional Public Company (Perumda) Pasar Kota Bitung in carrying out its operational activities and financial management. The internal control system is an essential component in ensuring effectiveness, efficiency, reliability of financial reporting, and compliance with regulations. This research employs a descriptive qualitative method, with data collection techniques including interviews, observations, and documentation involving the management and employees of Perumda Pasar Kota Bitung. The results show that the internal control system at Perumda Pasar Kota Bitung has been implemented quite well, particularly in the areas of control environment and control activities. However, there are still weaknesses in monitoring and in the information and communication system, especially in transaction recording and financial reporting, which are not yet fully integrated. The researcher recommends improving human resource capacity, implementing a more modern accounting information system, and conducting regular supervision to ensure the internal control system operates optimally.